Surgical treatment for synchronous multiple primary lung cancer: Is it possible to achieve both curability and preservation of the pulmonary function?. Issue 22 (30th September 2021) - Watanabe, Takuya; Tanahashi, Masayuki; Suzuki, Eriko; Yoshii, Naoko; Tsuchida, Hiroyuki; Yobita, Shogo; Iguchi, Kensuke; Uchiyama, Suiha; Nakamura, Minori
Abstract: Background: With the advent of high‐resolution chest imaging, the number of patients diagnosed with multiple primary lung cancers is increasing. For the treatment of multiple lung cancers, a surgical procedure that preserves pulmonary function while ensuring curability is required. Methods: The study population included 85 patients with synchronous multiple primary lung cancer who received surgical resection between January 2010 and September 2020. Patients with synchronous lung cancer within the same lobe were excluded, and only patients with ≥2 involved lobes were included. The postoperative pulmonary function was examined at 3–6 months after the surgery. Results: Sixty‐seven patients had cancers within the ipsilateral lobe, and 18 patients had cancers in bilateral lobes. Seventy‐six patients (89.4%) underwent combination surgery with limited resection (e.g., segmentectomy and wedge resection). The preoperative pulmonary functions (mean VC/%VC, mean FEV1 /%FEV1, and mean %DLCO) were 3.06 L/100.2%, 2.23 L/96.1%, and 117.2%, respectively, and the postoperative pulmonary functions were 2.45 L/81.4%, 1.87 L/81.2%, and 102.6%. In each parameter, the predicted reductions of pulmonary function were almost the same as the predicted values. The 5‐year survival rate was 85.0%. The 5‐year survival rate according to the most advanced pathological stage was 94.9% for stage I disease, and 62.6% for stage ≥II, which was a significant difference ( p < 0.001). Conclusions: Surgical treatment including limited resection, especially segmentectomy and wedge resection, for synchronous multiple primary lung cancer can preserve pulmonary function while ensuring curability. Abstract : Our method could adequately predict the postoperative pulmonary function, and the prognosis was good when combined with limited resection.